Administrasi Penjualan pada Divisi Keuangan PT Dimensi Citra Semesta - Zhusuf Falhamdany; Dyah Widowati (Lembaga Pengembangan Kinerja Dosen, 2024)
In selling goods, there is an administrative process that goes through in companies and the business world, starting from data input to archiving sales and financial file data. This process is carried out so that the goods sales files can be well organized. Therefore, this journal aims to determine the process of inputting and archiving sales and financial files in the sale of goods at PT Dimensi Citra Semesta. This journal uses interview and observation methods in sales flow, data input, and archiving sales and financial file data. Through this method can discover the technology used in data input and the steps in archiving structured files and sales data. The results of this journal show that there is a sales flow process starting from receiving the order until the goods are dispatched, after the goods are dispatched, there are data and files that are input and archived as files to be saved and easily searched if needed.